Treatment with lenalidomide (Revlimid®), cyclophosphamide (Endoxan®) and prednisone (REP) in relapsed/refractory multiple myeloma patients: results of a single centre retrospective study. Issue 2 (April 2014) - Zelis, N.; Devos, T.; Dierickx, D.; Janssens, A.; Raddoux, J.; Verhoef, G.; Delforge, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Lenalidomide (Revlimid®) combined with intermittent dexamethasone (the RD regimen) is one of the current standards for treatment of patients with relapsed/refractory multiple myeloma (MM). However, since the disease in the majority of patients will become resistant to RD, or treatment with RD needs to be discontinued due to side effects, we evaluated the combination lenalidomide, low-dose oral cyclophosphamide, with prednisone (REP) in patients with relapsed/refractory MM previously exposed to RD. For this purpose, we performed a single centre retrospective study of the efficacy of REP in 19 patients with relapsed/refractory MM. Overall response rate (partial response or better) with REP was 68% compared with 83% with RD, but with a shorter time to response with the triplet REP. Time to progression after REP was 6 months. Overall the REP regimen was better tolerated compared to RD. We conclude that the REP regimen is an effective treatment regimen for patients with relapsed/refractory MM with good tolerance, warranting further exploration in prospective randomized trials.